The impact of endometrioma and laparoscopic cystectomy on serum anti-Müllerian hormone levels - Li Sheng-Hsiang; Wu Frank; Hwu Yuh-Ming; Sun Fang-Ju; Lin Ming-Huei; Lee Robert (BMC, 2011)
Abstract Background Serum anti-Müllerian hormone (AMH) had been proposed as a marker of ovarian reserve. The aim of this study was to evaluate the impact of endometrioma and laparoscopic cystectomy on ovarian reserve as measured by serum AMH levels. Methods A total of 1,642 patients were recruited in this retrospective analysis. Control group (group 1) included 1,323 infertility patients without endometrioma. Endometrioma group (group 2) included 141 patients with ovarian endometrioma. Previous cystectomy group (group 3) included 147 patients who underwent unilateral or bilateral laparoscopic cystectomy due to ovarian endometrioma more than 6 months before enrollment. Current cystectomy group (group 4) included 31 patients who underwent cystectomy during study period. Serum anti-müllerian hormone (AMH) levels were measured upon enrollment with all patients. For patients in group 4, AMH levels were measured before and 3 months after cystectomy. Results Mean AMH level of patients in control group was significantly higher than that of endometrioma group or previous cystectomy group in each age subgroup, while the mean serum AMH level of the endometrioma group was also significantly higher than that of the previous cystectomy group in each age subgroup. The mean AMH level was significantly lower in patients with previous bilateral cystectomy compared to that of patients with unilateral cystectomy. The mean serum AMH level was also significantly lower in patients with bilateral endometrioma compared to that of patients with unilateral endometrioma. In group 4, mean AMH level significantly decreased from 3.95 +/- 0.42 preoperation to 2.01 +/- 0.21 ng/ml at 3-month postoperation. Conclusions Both ovarian endometrioma and cystectomy are associated with a significant reduction on ovarian reserve. Bilateral endometrioma exerts a more profound negative impact on ovarian reserve than unilateral endometrioma, regardless of either conservative or surgical intervention.